GIS and satallite applications for piracy-monitoring - Josh Lyons (Freedom from Fear, 2009)
Without a central government, for nearly two decades the people of Somalia have had to cope with natural disasters, civil war and humanitarian crisis as best as they can, often resorting to informal and illegal economic activities for survival. Although the origins of Somali maritime piracy remain obscured, it is likely that this was a response of Somali fishermen to the illegal, unreported and unregulated (IUU) fishing within their territorial waters by foreign companies who sought to capitalize on the lack of a national coast guard in the 1990s.